(untitled) (Sains Humanika, 2013)
This study investigates the perceptions of users of financial statement regarding the importance of items in indices of internet financial reporting (IFR). This study adopts the questionnaire survey method in order to seek the view of users of financial statement, particularly on the importance of items that to be included in the checklist of IFR indices. From a comprehensive review of the IFR literature, the level of IFR in this study can be categorized into two dimensions namely the ‘content’ and ‘presentation’. The findings show that the five most important items which are income statement of current year, cash flow statement of current year, balance sheet of current year, annual report of current year (full text), and auditor report of current year can explain the dimension of content. Meanwhile, the five most important items for the dimension of presentation which are annual report in PDF format, loading time of the website, link to homepage, hyperlinks inside the annual report, and link to table of contents. Results of the study also provide empirical evidence that 144 disclosure items can be used for the checklist of IFR indices to measure the level of IFR. The finding provides an insight into the IFR practice in Malaysia. Implications of these findings and future research directions are also discussed in this study.